Comprehensive mathematical modelling of a lightweight flexible link robot manipulator. (2nd January 2008) - Loudini, Malik; Boukhetala, Djamel; Tadjine, Mohamed
This paper deals with a comprehensive study of the application of the Timoshenko Beam Theory (TBT) concepts to the mathematical modelling of a planar lightweight single link flexible robot manipulator arm pinned at its actuated base and carrying a payload at its free end-point. The emphasis being essentially set on obtaining accurate and complete equations of the transversely vibrating motion that display the most relevant aspects of structural properties inherent to the modelled lightweight flexible link, two important damping mechanisms, internal structural viscoelasticity (Kelvin-Voigt damping) and external viscous air damping, have been included in addition to the TBT classical effects of cross section shear deformation and rotational inertia. Torsional, gravitational and longitudinal elongation effects have been neglected. Digital simulations are performed to show the free vibrational behaviour of the modelled robotic system.